Short-term effect of low-dose roxadustat combined with erythropoiesis-stimulating agent treatment for erythropoietin-resistant anemia in patients undergoing maintenance hemodialysis - Xu, Qiaoying; Huang, Jingjing; Liu, Qingzhen; Wang, Xueling; Liu, Haiying; Song, Yan; Dou, Fulin; Lv, Shasha; Liu, Gang (Frontiers in Endocrinology, 2024)
Erythropoietin resistance is present in some patients with chronic kidney disease, especially in those undergoing hemodialysis, and is often treated using roxadustat rather than iron supplements and erythropoiesis-stimulating agents (ESAs). However, some patients cannot afford full doses of roxadustat. This retrospective study investigated the efficacy of low-dose roxadustat combined with recombinant human erythropoietin (rhuEPO) therapy in 39 patients with erythropoietin-resistant renal anemia undergoing maintenance hemodialysis (3-4 sessions/week).The ability of the combination of low-dose roxadustat and rhuEPO to increase the hemoglobin concentration over 12 weeks was assessed. Markers of iron metabolism were evaluated. Eligible adults received 50-60% of the recommended dose of roxadustat and higher doses of rhuEPO.The mean hemoglobin level increased from 77.67±11.18 g/dL to 92.0±8.35 g/dL after treatment, and the hemoglobin response rate increased to 72%. The mean hematocrit level significantly increased from 24.26±3.99% to 30.04±3.69%. The soluble transferrin receptor level increased (27.29±13.60 mg/L to 38.09±12.78 mg/L), while the total iron binding capacity (49.22±11.29 mg/L to 43.91±12.88 mg/L) and ferritin level (171.05±54.75 ng/mL to 140.83±42.03 ng/mL) decreased.Therefore, in patients with ESA-resistant anemia who are undergoing hemodialysis, the combination of low-dose roxadustat and rhuEPO effectively improves renal anemia and iron metabolism.